Creatine monohydrate intervention on the cardiovascular fitness, body composition, aerobic and anaerobic performance and total energy expenditure among adults - Amani, Alireza (2012)
While safety and health concerns have been raised by various professional groups regarding creatine supplementation, no study has reported any effect form creatine supplementation on the cardiovascular fitness and adults population. The aim of this study was to assess the effect of creatine monohydrate on the aerobic and anaerobic performance, cardio vascular function during high intensity aerobic exercise, total energy expenditure and cardiovascular risk factors. Creatine monohydrate has been known as a popular supplement among athletes. The effect of the creatine monohydrate on the anaerobic performance has been studied, although, its effects on the cardiovascular fitness aspect need to be investigated deeply. The present study was conducted to carry out four steps on the postgraduate students in UPM. A total number of 354 male and female UPM students were participated in this research. At the first step, using an online survey, the consumption of creatine monohydrate and other supplements was studied. According to the survey, creatine was not a popular supplement among the students. At the second phase, the effect of creatine monohydrate on the cardiovascular fitness was examined. For this purpose, the effect of creatine monohydrate on the cardiovascular risk factors including lipoproteins profile and homocysteine concentration was investigated. An increase in HDL concentration was shown in the result of creatine consumption, although, this effect was not statistically significant. The data also showed no significant change in the blood level of LDL and homocysteine in the creatine-treated group compared to the controls. It was also shown that stroke volume during the high intensity aerobic exercise can be increased with creatine supplementation, while at the placebo group showed a decrease in the same condition. However, this difference was not statistically significant. Increasing in the body mass index and body fat percent was observed in the creatine-treated group. Significant effect of creatine supplement on the total energy expenditure during high intensity aerobic exercise was also revealed. Analysing data by manova also has shown that there was not posetive effect by creatine supplement on group of DV (Fat free mass, Body mass index, Body fat percent, Stoke Volume,Homocysteine, Low density lipoprotein and High density lipoprotein) as the cardiovascular fitness parameters. At the next section of the research, the effect of creatine monohydrate in combined with resistance exercises on anaerobic and aerobic performance was investigated. Data analysis showed no significant effect of creatine consumption on the anaerobic and aerobic performance of the participants. The most obvious finding of the present study was demonstrating some other aspect of creatine monohydrate in effecting on the human body, specifically for inactive adults. However, to make better the other aspects of creatine monohydrate in the human body, more experimental researches are recommended.